T Cell Repertoire and Inflammatory Bowel Disease - Kenneth Croitoru; David KH Wong; Maria E Baca-Estrada (Canadian Journal of Gastroenterology)
The diversity of the T cell receptor repertoire is generated through rearrangement of the variable, junctional and constant region genes. Selection processes in the thymus and periphery serve to eliminate self-reacting T cells, thereby preventing autoimmune disease. The possibility that inflammatory bowel disease (IBD) is an autoimmune disease has led to the search for an auto-antigen. In addition, studies are exploring the T cell receptor repertoire in IBD patients for changes that may provide clues regarding etiopathogenesis. Using monoclonal antibodies to T cell receptor variable-gene products or polymerase chain reaction analysis of variable-gene mRNA expression, the mucosal T cell repertoire has been examined in humans. The intestinal intraepithelial lymphocytes show a significant degree of oligoclonal expansion that may represent local antigen exposure or unique selection processes. This is in keeping with studies that show that murine intestinal intraepithelial lymphocytes undergo positive and possibly negative selection independent of the thymus. In the inflamed human gut, shifts in the T cell receptor repertoire may also reflect recruitment of peripheral T cells to the gut. In one study, a subset of Crohn’s disease patients was shown to have an increase in the proportion of variable β8 peripheral blood lymphocyte and mesenteric lymph node cells, suggesting a superantigen effect. The authors hypothesized that changes in the functional T cell receptor repertoire can also occur which might be independent of changes in the distribution of T cells expressing variable β T cell receptors. In fact, the authors have shown there is a selective decrease in the cytotoxic function of peripheral variable β8 T cells in Crohn’s disease. Furthermore, stimulation with the variable β8 selective bacterial enterotoxin staphylococcal enterotoxin E failed to increase the cytotoxic function in this subset of Crohn’s disease patients compared with controls. This suggests that in Crohn’s disease, variable β8 T cells have undergone an alteration in function that may reflect previous exposure to a superantigen-like stimulus. The relationship to the etiology and pathogenesis of IBD remains to be defined.